PENGUATAN CINTA TANAH AIR MELALUI STORYTELLING UNTUK ANAK-ANAK PEKERJA MIGRAN DI PULAU PINANG, MALAYSIA - Hutagalung, Simon; Nizar, Moh; Rakhmadi, Robi (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This community service program aims to strengthen the sense of patriotism among Indonesian migrant workers’ children in Penang, Malaysia. Many of these children grow up in foreign environments with minimal exposure to Indonesian culture, making them prone to losing their national identity. This activity utilizes storytelling as a medium to instill nationalistic values and deepen their understanding of Indonesian culture and history. Storytelling was chosen because it is engaging and easy for children to understand, especially through interactive activities like role-playing and discussion. The children actively engage in the stories, participate in dialogue, and share their views on the meanings embedded within them. Facilitators also use visual aids and puppet characters to enhance messaging and increase participation. Evaluation is conducted through direct observation, interviews, and involvement in creative activities. The results show positive changes in the children’s understanding and attitudes towards national values, as well as a stronger sense of pride in their Indonesian identity. The children become more open to diversity, demonstrate a spirit of togetherness, and show respect for other cultures. This program has successfully fostered a stronger emotional connection to national values among these migrant children, which is expected to contribute to their character development as future citizens.